Indicators of cognitive activity of children with laboratory hypothyroidism - Snizhana Sokolnyk; Dmytro Kolesnik; Dmytro Nechytaylo; Iryna Sokolnyk; Lyudmyla Khlunovska; Iryna Loziuk; Valentyna Ostapchuk (Kazimierz Wielki University, 2021)
The growth rate of a healthy child, the peculiarities of its physical and intellectual development, the formation of reproductive function are largely determined by the state of the endocrine system. Thyroid hormones have a significant impact on the growth and development of the child's organism. Today, attention is focused on the consequences of intellectual disabilities in children with hypothyroidism, as well as the impact of chronic iodine deficiency in the environment on the development of children. Insufficient intake of iodine in the body leads to congenital dysontogenesis of higher mental functions, to the formation, in severe cases, of mental retardation of varying degrees, and, in mild forms - to the borderline or partial disorders of intelligence. The aim is to study the cognitive functions of children with laboratory hypothyroidism. Methods. For a screening study of the intellectual development of school-age children living in geographical areas of Chernivtsi region (Ukraine) with varying degrees of iodine supply, 399 schoolchildren aged 11-18 years were studied, including 194 boys and 205 girls. The main group consisted of children (99) with laboratory hypothyroidism (HL), with thyroid stimulating hormone (TSH) elevation or with diverse complaints and who had been found to have elevated TSH levels during routine examinations. Patients with any kind of systemic disease and/or taking medications were excluded from the study. Diagnosis of HL was based on mild increase of TSH (5-25mIU/L) with a normal fT4 level. Thyrotropin-releasing hormone (TRH) test was also performed in all children. TSH response to TRH stimulation was considered to be normal when TSH levels were between 5-25 mIU/L. The formation of intellectual function was determined using a fragment of the R. Kettel test (adapted modified version of the children's personality questionnaire R. Kettel). Іnclusion сriteria: age 11-18 years, living in the Chernivtsi region, the absence of organic pathology of the CNS and mental retardation, diseases of the eyesight and hearing, for 6 months, all subjects did not receive any treatment with iodine-containing drugs and thyroid hormones. Results. Analysis of the study results showed that children, for the most part, have an average degree of intellectual development (60%). The level of intellectual formation changed in the direction of decreasing with increasing degree of iodine deficiency. Among children with laboratory hypothyroidism, the number of those who had a low level of intelligence was almost twice as high as in children from the comparison group 25 [21.8-27.3] % against 13 [11.8-16.6] %, P < 0.01). Children with laboratory hypothyroidism have a "debt" of 56% of attention, 36% of perception, 26% of motility, and 44% of memory. The pace of operating activities was reduced by 26%. Comparison of TSH concentration, ioduria and thyroid volume with the presence or absence of deficits in certain cognitive functions showed that in children with laboratory hypothyroidism and fine motor skills TSH G level was increased by 90%, thyroid volume by 28% , and with memory loss - 125% and 38%, respectively. Correlative analysis revealed a highly probable positive relationship between moderate strength in prepubertal children between thyroid volume and fine motor skills (r = 0.485, P < 0.01), memory (r = 0.488, P < 0.05) and efficiency (r = 0,321, P < 0,05). Conclusion. Children with subclinical hypothyroidism are characterized by decreased memory, instability of attention and decreased ability to concentrate, impaired fine motor skills, which generally reduces their mental capacity.